Pengaruh latihan boomerang RUN dan latihan laterai RUN terhadap peningkatan kelincahan atlet sepak bola usia 13 tahun - Zam Zani; Maulidin; Ismail Marzuki (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This study aims to determine the effect of Boomerang Run and Lateral Run training on improving the agility of 13-year-old football athletes at Narmada Football Academy (NFA). Agility is a crucial component in modern football, enabling players to quickly change direction, maintain balance, and support both offensive and defensive skills. The research method used is an experimental design with a pre-experimental one-group pretest-posttest approach. The sample consisted of 16 NFA athletes divided into two treatment groups. The Illinois Agility Run test was used as an instrument to measure agility before and after the training intervention. Results from the paired sample t-test showed a significant improvement in both groups. The Boomerang Run training reduced the average agility time from 25.60 seconds to 23.35 seconds, while the Lateral Run training reduced the average from 23.35 seconds to 22.46 seconds. The findings indicate that both training methods significantly enhance agility, with a notable difference in effectiveness between the two. This research provides valuable insights into agility training strategies for youth football players